Use of Telemedicine to Provide Initial Home Parenteral Nutrition Training During COVID-19 Pandemic. (14th June 2022) - Elfadil, Osman Mohamed; Mundi, Manpreet; Hurt, Ryan; O'Donnell, Katherine; Hager, Channelle; Bonnes, Sara; Salonen, Bradley
Abstract: Objectives: Coronavirus Disease 2019 (COVID-19) has led to dramatic changes including social distancing, closure of schools, travel bans, and issues of stay-at-home orders. The health-care field has been transformed with elective procedures and on-site visits being deferred. Telemedicine has emerged as a novel mechanism to continue to provide care. However, there remains a paucity of data regarding its efficacy in nutrition support especially in patients with chronic intestinal failure (CIF). Methods: The current abstract presents our experience with the use of telemedicine to provide training for home parenteral nutrition (HPN). Results: Since the onset of COVID-19 pandemic, we have successfully provided virtual training in three patients including two who were noted to be severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) positive and one patient who could not be transferred to our facility for training. For SARS-CoV-2 positive patients, risk of transmission to nursing staff with 8–10 hours of face-to-face training in two cases was felt to be too significant for in person training. We determined that best option would be stabilize PN in the hospital and perform virtual training. Although, virtual training was successfully performed, it was felt that training in this manner took much longer, required frequent adjustment of the tablet device to ensure patient remained in field of view, and made it difficult to connect with the patient emotionally. Conclusions: Telemedicine has significantly improved care provided during COVID-19; however, it should be used in a manner that compliments but does not supplant standard care. Funding Sources: None.